THEOREM OF THEODOR ADORNO ON HEGEMONY, MUSIC CRITICISM, AND FOLK MUSICAL STUDIES - Kesia Rosalina Putri; Sapta Lelunu, Nia Olivia, Daniel, Octa Maria Sihombing (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2024)
This research aims to demonstrate that there is music thinking as a resistance or non-violent resistance that is based on the balance of life through musical works. In order to realize the research objectives, Theodor Adorno's thoughts have become essential to explore, analyze and make Adorno's thoughts as the basis for criticism of music which prioritizes music as merely personal satisfaction but excludes certain subjects or groups. This study is qualitative research with library sources through journals as part of the secondary sources. In addition to secondary sources, books written by Theodor Adorno became the main material as the basis for analysis of music secularization and resistance. Results have shown that Theodor Adorno's thoughts on the basis of music hegemony in the public sphere become weapons of the self and outside the self as tools of resistance to find glimmers of hope through reflection through and in music universally.